Dynamics of Soil Carbon Average Content at Different Depths: Insights from a Global Approach to Climate Change Mitigation - Rodrigues, Cristina I. Dias (2025)
This study provides an in-depth examination of the average values of gravimetric carbon content, measured in grams per kilogram (g/kg), and the organic Carbon (OC) content, quantified in kilograms per square meter (kg/m2), within various soil classifications and depths. Highlighting the relevance of such research, it delves into the intricacies of soil OC dynamics across diverse depth strata and offers a comparative analysis of different soil types, each with distinct carbon sequestration capacities. Utilizing the latest version of the world soil database, the research integrates three interconnected data sets: soil classification, density, and OC. In total, the study includes 51,507 soil profile layers to calculate the average gravimetric OC content in the fineearth fraction. In parallel, the average OC content in the fine-earth fraction was determined across 6,197 soil profile layers. This comprehensive data is organized into 34 separate soil units, each dissected across four depth categories: 0–30 cm, 0–100 cm, 0–200 cm and 0–2590 cm. The findings from this analysis reveal a consistent pattern: as depth increases, both the gravimetric content and average OC content tend to decrease. However, it is noteworthy that this trend is not universal. Certain soil units demonstrate an opposing behavior, with an increase in average OC content observed at greater depths, contradicting the prevailing trend. This divergence underscores the complexity of soil OC dynamics and the inherent variability across different soil units.